2021
DOI: 10.7759/cureus.19548
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Chemical and Mechanical Prophylaxis of Venous Thromboembolism in Non-surgical Mechanically Ventilated Patients

Abstract: To compare the efficacy of mechanical and chemical prophylaxis in non-surgically mechanically ventilated patients in terms of reduction in mortality and length of hospital stay. A total of 200 patients admitted to intensive care units (ICUs) were recruited retrospectively. Half participants received mechanical prophylaxis and half received chemical prophylaxis. Patients with medical diseases with age 18 years or above, both genders, Pakistani nationals, receiving mechanical ventilation for more than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
(36 reference statements)
1
0
0
1
Order By: Relevance
“…In this study, pharmacological prophylaxis was associated with lower prevalence of VTE, which might show that pharmacological prophylaxis was more effective than mechanical prophylaxis or use in both to prevent VTE. The results were similar to the existing research, which indicated that anticoagulants can effectively prevent blood hypercoagulability via the inhibition of thrombin and coagulation factors, and consequently prevent VTE [65]. As also found in previous studies, the SAPS II was associated with disease severity, and the higher the SAPS II score, the more serious the disease [66].…”
Section: Discussionsupporting
confidence: 91%
“…In this study, pharmacological prophylaxis was associated with lower prevalence of VTE, which might show that pharmacological prophylaxis was more effective than mechanical prophylaxis or use in both to prevent VTE. The results were similar to the existing research, which indicated that anticoagulants can effectively prevent blood hypercoagulability via the inhibition of thrombin and coagulation factors, and consequently prevent VTE [65]. As also found in previous studies, the SAPS II was associated with disease severity, and the higher the SAPS II score, the more serious the disease [66].…”
Section: Discussionsupporting
confidence: 91%
“…Outrossim, merece destaque a profilaxia farmacológica com drogas anticoagulantes, as quais, ao inibir a ação da trombina e fatores de coagulação, são capazes de prevenir a hipercoagulabilidade sanguínea e consequentemente o risco de TEV (AJMAL et al, 2021). De acordo com a Sociedade Americana de Hematologia, a terapia anticoagulante é recomendada para pacientes sem alto risco de sangramento, haja vista que estas drogas aumentam o risco de hemorragias (SCHÜNEMANN et al, 2018).…”
unclassified